2021
DOI: 10.1103/physreva.104.012405
|View full text |Cite
|
Sign up to set email alerts
|

One qubit as a universal approximant

Abstract: A single-qubit circuit can approximate any bounded complex function stored in the degrees of freedom defining its quantum gates. The single-qubit approximant presented in this work is operated through a series of gates that take as their parameterization the independent variable of the target function and an additional set of adjustable parameters. The independent variable is re-uploaded in every gate while the parameters are optimized for each target function. The output state of this quantum circuit becomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…In Ref. [61], it was observed that gate sequence R 2 (x, ω, Φ 2 ) := 4(q+1) , can encode certain finite Fourier series into its matrix components. Here, not only do we formally prove that for any target series but also we provide an explicit, efficient recipe for finding the adequate choice of pulses Φ 2 .…”
Section: Single-qubit Qsp Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [61], it was observed that gate sequence R 2 (x, ω, Φ 2 ) := 4(q+1) , can encode certain finite Fourier series into its matrix components. Here, not only do we formally prove that for any target series but also we provide an explicit, efficient recipe for finding the adequate choice of pulses Φ 2 .…”
Section: Single-qubit Qsp Methodsmentioning
confidence: 99%
“…( 18) is then no longer valid and one must assess the query complexity on a case-bycase basis. This can for instance be tackled numerically by variationally optimising the gate sequence R 2 (x, ω, Φ 2 ) to block-encode the periodic extension of f [61]. Either way, clearly, if a normalized Fourier expansion is a-priori available, one can skip steps 1 to 3 in Alg.…”
Section: (21a) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is promising, though its utility depends on the existence of large-scale quantum computers with low gate errors and enough qubits to perform quantum error correction. More recent proposals focus on defining a quantum neural network (QNN), or parameterized quantum circuit [13][14][15][16], which then can be trained to implement a function class [17][18][19]; these proposals can be implemented on current NISQ-era devices. For example, several QNNs have been proposed for pattern classification [20][21][22][23] or data compression [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the classical domain, expressivity is guaranteed by the universal approximation theorem, which requires a nonlinear activation function for the perceptrons in the network. In the quantum setting, it has been shown that similar notions of universal approximation exist for functions mapping gate parameters to the state prepared by the quantum circuit [16]. However, currently there is no universally accepted way to extend the concept of classical neural networks to quantum systems [17,18].…”
Section: Introductionmentioning
confidence: 99%